Does vibration training reduce the fall risk profile of frail older people admitted to a rehabilitation facility? A randomised controlled trial. Issue 11 (21st May 2016) - Parsons, J.; Mathieson, S.; Jull, A.; Parsons, M.
Abstract: Purpose: To determine the effect of Vibration Training (VT) on functional ability and falls risk among a group of frail older people admitted to an inpatient rehabilitation unit in a regional hospital in New Zealand. Method : A randomized controlled trial of 56 participants (mean 82.01 years in the intervention group and 81.76 years in the control group). VT targeting lower limb muscles with a frequency 30–50 Hz occurred three times per week until discharge. Amplitude progressively increased from 2 to 5 mm to allow the programme to be individually tailored to the participant. The control group received usual care physiotherapy sessions. Outcome measures were: Physiological profile assessment (PPA); and Functional Independence measure (FIM) and Modified Falls Efficacy Scale (MFES). Results : There was a statistically significant difference observed between the two groups in terms of FIM score ( F = 5.09, p = 0.03) and MFES ( F = 3.52, p = 0.007) but no difference was observed in terms of PPA scores ( F = 0.96, p = 0.36). Conclusions : Among older people admitted to an inpatient rehabilitation facility there may be some beneficial effect to the use of VT in conjunction with usual care physiotherapy in terms of improved functional ability. The study design and the small dosage of VT provided may have precluded any change in falls risk among participants. Implications for Rehabilitation: Vibration training (VT) may assist in reducing the risk of falling among at risk older people. Current pressures on health systems (ageing population, reduced hospital length of stay) necessitate the development of innovative strategies to maximise the rehabilitation potential of older people. Among older people admitted to an inpatient rehabilitation facility there may be some beneficial effect to the use of vibration training in conjunction with usual care physiotherapy in terms of improved functional ability.